Pengaruh Model Problem Based Learning Berbasis Open Ended Terhadap Kemampuan Berfikir Kritis Siswa dalam Memecahkan Masalah Pelajaran Matematika - Juwanto, Ebby; Ramadhani, Efran; Ali Fakhrudin, Ali Fakhrudin (Indonesian Research Journal on Education, 2023)
The problem in this research is that the effect of the Problem Based Learning model based on Open Ended is unknown on students' critical thinking skills in solving math problems. The purpose of this study was to determine students' critical thinking skills in solving problems in mathematics before, and after the implementation of the Open-Ended-based Problem Based Learning model for class Vat SDN 2 Epil. The type of research used is quantitative research, the type of research used is Quasi Experimental Design. The sample in this study was class V students, totaling 32 students. The technique used for data collection in this study was observation, using data and written tests. This research instrument is real, using observation and written tests. Based on the results obtained, it can be concluded that the critical thinking skills of fifth grade students of SDN 2 Epil in mathematics using an Open-Ended-based Problem Based Learning model have increased in the circumference and area of the trapezoid material. This can be seen from the results of the students' average scores where the experimental group class obtained data (4.218%) and the control group (1.681%) because tcount > ttable (4.218 > 1.681).